COMPLEMENTARY FEEDING - A SHORT REVIEW OF SEVERAL CORRECT PRINCIPLES OF LONG-TERM HEALTH - Oana-Raluca Temneanu; Dana-Elena Mindru; Nistor Nicolai (Amaltea Medical Publishing House, 2015)
Nutrition epitomizes the whole range of physiological processes of absorbtion and decomposition of food in the body, as required for growth and development. The debates on the feeding trends are topical, a large number of scientifi c boards and international committees fully concentrate on the impact of correct feeding on growth and harmonious development, starting even from intrauterine life. The progressive introduction of half solid and solid food in the infant's diet after 4-6 months, gradually replacing the milk meals previously administered is known as diversifi ed (complementary) feeding. The latest recommendations of the ESPGHAN Committee (European Society for Pediatric Gastroenterology, Hepatology and Nutrition) regarding the moment of switching from an exclusively milk diet to a diet which includes other foods is included in the period of time between week 17 and 26. The compliance and the collaboration of the family with the doctors are of paramount importance. Considering the present day open access to a lot of information, sometimes without any scientifi c basis, we believe it is opportune to review briefl y the main aspects of the complementary feeding according to the recommendations in the field.